Maternal mortality assessment in a tertiary care hospital in Uttar Pradesh, India - Singh, Urvashi Barman; Jain, Shakti; Srivastava, Yashi; Gupta, Manisha; Dayal, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Objective of this study was to calculate the maternal mortality rate in our hospital and to assess the epidemiological aspects and causes of maternal mortality to further analyse ways to reduce the maternal mortality rate (MMR). Methods: This was a retrospective analytical study done in the department of obstetrics and gynecology, MLN Medical College and District Women Hospital, Prayagraj over a time period of 10 years i.e., October 2009 to October 2019. Retrospective analysis and evaluation of the medical records and statistics was done to find out and collect specific causes of maternal deaths in the give time period. Results: There were 357 maternal deaths from October 2009 to October 2019. Maternal mortality rate in the study was calculated to be 498.42 per 1 lakh live births. Maximum deaths were in 21-30 years age group with multipara, unbooked and illiterate cases. Majority of the deaths reported were from direct causes of maternal mortality i.e., hemorrhage, hypertensive disorders and sepsis. Conclusions: In the selected hospitals, the mean maternal mortality rate in the study period was 498.42/100000 births. 71.4% had direct cause and 21.56% had indirect cause of maternal mortality several factors like regular antenatal visits, early identification of high-risk cases, timely referral, institutional deliveries, adequate post-partum care and follow-up can contribute to decrease the maternal mortality rate effectively.